Mechanistic Studies on the Substrate-Tolerant Lanthipeptide Synthetase ProcM - Mukherjee, Subha (American Chemical Society, 2014)
[Image: see text] Lanthipeptides are a class of post-translationally modified peptide natural products. They contain lanthionine (Lan) and methyllanthionine (MeLan) residues, which generate cross-links and endow the peptides with various biological activities. The mechanism of a highly substrate-tolerant lanthipeptide synthetase, ProcM, was investigated herein. We report a hybrid ligation strategy to prepare a series of substrate analogues designed to address a number of mechanistic questions regarding catalysis by ProcM. The method utilizes expressed protein ligation to generate a C-terminal thioester of the leader peptide of ProcA, the substrate of ProcM. This thioester was ligated with a cysteine derivative that resulted in an alkyne at the C-terminus of the leader peptide. This alkyne in turn was used to conjugate the leader peptides to a variety of synthetic peptides by copper-catalyzed azide–alkyne cycloaddition. Using deuterium-labeled Ser and Thr in the substrate analogues thus prepared, dehydration by ProcM was established to occur from C-to-N-terminus for two different substrates. Cyclization also occurred with a specific order, which depended on the sequence of the substrate peptides. Furthermore, using orthogonal cysteine side-chain protection in the two semisynthetic peptide substrates, we were able to rule out spontaneous non-enzymatic cyclization events to explain the very high substrate tolerance of ProcM. Finally, the enzyme was capable of exchanging protons at the α-carbon of MeLan, suggesting that ring formation could be reversible. These findings are discussed in the context of the mechanism of the substrate-tolerant ProcM, which may aid future efforts in lanthipeptide engineering.